Apóstolos de Maynas a ação jesuítica no Solimões no diário do Padre Samuel Fritz - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The purpose of this paper is to analyze the action in the Jesuit Missions Maynas through the way they were represented in the Diary of Father Samuel Fritz. In this sense, there were several factors that influenced this action, a priori, it is the understanding of the characteristics of Jesuit education and the axes formed articulated their identity, ie his way of proceeding. Then we analyze the influences of the Spanish Patronato in this action, together with the recommended guidelines on the Councils of Trent and Lima. Finally, we demonstrate that despite the various difficulties mentioned in the Journal, the action of the Jesuit college of Quito in the Amazon last until the expulsion of them from Peru. And that collaborate to redesign a new reality on the banks of the Solimoes River, since various ethnicities followed Father Fritz surpassing the confusing borders of Brazil settling in Peru. Those who remained were incorporated into the administrative Portuguese, but the formation of new settlements were based on the old reductions created by Fritz.
Keywords: Missões de Maynas; Jesuítas; Indígenas; Catequese; Fronteira; Missions Maynas; Jesuits; Indigenous; Catechesis; Border; CIÊNCIAS HUMANAS: HISTÓRIA